2005
DOI: 10.1111/j.1539-6924.2005.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

The Greater Ability of Graphical Versus Numerical Displays to Increase Risk Avoidance Involves a Common Mechanism

Abstract: By displaying a risk reduction of 50% graphically rather than numerically, Stone, Yates, and Parker significantly increased professed risk-avoidant behavior. The current experiments replicated this effect at various risk ratios. Specifically, participants were willing to spend more money to reduce a risk when the risk information was displayed by asterisks rather than by numbers for risk-reduction ratios ranging from 3% to 97%. Transforming the amount participants were willing to spend to logarithms significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 19 publications
5
68
0
Order By: Relevance
“…Even in such matrix displays, format can strongly affect behavior and judgment. For example, graphs that display the number affected (numerator) without showing the total number at risk (denominator) are more effective in promoting risk-reducing behavior (Schirillo & Stone, 2005; Stone et al, 2003). Highlighting the figures affected by disease in a random arrangement produced larger estimates of risk magnitude than arranging them sequentially (Schapira, Nattinger, & McAuliffe, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Even in such matrix displays, format can strongly affect behavior and judgment. For example, graphs that display the number affected (numerator) without showing the total number at risk (denominator) are more effective in promoting risk-reducing behavior (Schirillo & Stone, 2005; Stone et al, 2003). Highlighting the figures affected by disease in a random arrangement produced larger estimates of risk magnitude than arranging them sequentially (Schapira, Nattinger, & McAuliffe, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies have shown that visual aids improve risk understanding (e.g., Galesic, Garcia-Retamero, & Gigerenzer, 2009;Garcia-Retamero & Galesic, 2010b;Lipkus, 2007;Lipkus & Hollands, 1999;Paling, 2003), reduce errors induced by anecdotal narratives (Fagerlin, Wang, & Ubel, 2005) and biases such as denominator neglect (e.g., GarciaRetamero & Dhami, 2011; On Avoiding Framing Effects 6 Gigerenzer, 2010;Okan, Garcia-Retamero, Cokely, & Maldonado, 2012), as well as increase risk avoidance (Schirillo & Stone, 2005). Finally, risk information presented via visual aids is perceived to be easier to understand (Goodyear-Smith et al, 2008) and recall (Gaissmaier et al, 2011).…”
Section: Using Visual Aids To Reduce Framing Effectsmentioning
confidence: 99%
“…70,71 In addition, risk information presented via visual aids is perceived as easier to understand 72,73 and has been shown to substantially increase risk avoidance. 74 What is still an open question is whether visual aids can reduce framing effects. Which visual aids, if any, are particularly effective has also not been investigated.…”
Section: Introductionmentioning
confidence: 99%